A case report of atraumatic splenic rupture after coronary stenting and dual antiplatelet therapy: Causality or relationship?. (November 2021) - Boccanelli, Paolo; Materazzo, Marco; Venditti, Dario; Pellicciaro, Marco; Santori, Francesca; Grande, Michele
Abstract: Introduction and importance: Atraumatic splenic rupture(ASR) is a rare event with challenging management, due to absence of clinical history of trauma and delayed diagnosis. Current clinical report could provide detailed information regarding clinical presentation and management to physicians. Case presentation: A 61 years-old woman underwent percutaneous coronary intervention(PTCA) after ST elevation myocardial infarction(STEMI). In the first day after PTCA epigastric abdominal disconfort was reported, and new PTCA excluded early complication. During hospitalization, due to anemization and hypotension CT scan was performed which revealed ASR with large hemoperitoneum. Emergency surgical splenectomy was performed. Postoperative course was uneventful and patient started 90 mg Ticageclor twice daily in the first post-operative day(POD) plus low molecular weight Heparin and restarted dual antiplatelet therapy(DAPT) the seventh POD. During follow up, patient underwent to assessment of platelet function showing normal level of DAPT inhibition. Due to the lack of pathological aggregation activity, DAPT was maintained. Clinical discussion: ASR is mainly linked to oncological, malformative, inflammatory and thromboembolic conditions. Despite anticoagulant and anti-aggregating drug-related ASR has been already described, we report the first case of drug-related ASR as immediate complication of PTCA due to DAPT. After surgery, careful anti-aggregating management was required to balance in stent restenosis and hemorragic risk. Assessment of platelet activity was performed to design a tailored anti-aggregating therapy. Conclusion: Drug-related ASR is dangerous complication due to the high mortality rate and misleading symptoms. After major bleeding events, such as drug-related ASR, evaluation of platelet function could provide a tailored DAPT. Highlights: Atraumatic splenic rupture (ASR) is a rare event with misleading symptoms. Our report describes the first case of ASR as an early complication after stenting. Aggregation test could support a tailored therapy to avoid further bleeding events.